AC breakdown strength of N/sub 2/, SF/sub 6/ and a mixture of N/sub 2/+SF/sub 6/ containing a small amount of SF/sub 6/ - Mardikyan, K.; Kalenderli, O.; Ersen, O.; Canarslan, E. (IEEE, 2002)
AC breakdown strengths of N/sub 2/, SF/sub 6/ and a mixture of N/sub 2/+SF/sub 6/ containing 1% of SF/sub 6/ were experimentally studied. For this purpose, 50 Hz AC breakdown voltages in both uniform and nonuniform fields up to a pressure of 400 kPa from 50 kPa were measured. Test results show that the addition of 1% of SF/sub 6/ to nitrogen increases the breakdown voltage up to 250 kPa in a nonuniform field. The relative breakdown strength of the mixture with respect to components was also calculated in 50 Hz AC voltage. The analysis of Paschen curves reveals an improvement of 40% in the breakdown strength of mixture in uniform field but in nonuniform fields, the maximum AC breakdown voltage of the mixture is 24% lower than that of pure SF/sub 6/.